2012
DOI: 10.1525/mp.2012.30.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Distortions in Reproduction of Two-Interval Rhythms: When the “Attractor Ratio” Is Not Exactly 1:2

Abstract: when rhythms consisting of two unequal intervalsare reproduced cyclically, their interval ratio tends to be distorted in the direction of 1:2 (= 0.5), which thus seems to function as an "attractor ratio" (AR). However, recent results for musicians in a synchronization task (Repp, London, & Keller, 2011) have suggested an upward-shifted AR (USAR) somewhat greater than 0.5. Three new experiments suggest that this shift is not due to synchronization versus continuation tapping, the range of interval ratios employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…If these deviations of the intersections from the 1:3:2 attractor were statistically reliable (we did not assess this), they would suggest an attractor in the vicinity of 1:3:2 whose interval ratios are not simple. In studies of musicians' production and perception of two-interval rhythms, Repp et al (2011Repp et al ( , 2012 recently found that the attractor deviated significantly from 1:2. Similar deviations from simple-ratio attractors for three-interval rhythms thus are conceivable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these deviations of the intersections from the 1:3:2 attractor were statistically reliable (we did not assess this), they would suggest an attractor in the vicinity of 1:3:2 whose interval ratios are not simple. In studies of musicians' production and perception of two-interval rhythms, Repp et al (2011Repp et al ( , 2012 recently found that the attractor deviated significantly from 1:2. Similar deviations from simple-ratio attractors for three-interval rhythms thus are conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…Even highly trained musicians tapping in synchrony with an exact auditory rhythm template show these distortions, which thus seem to be almost unavoidable. Recent investigations have suggested that the attractor for musicians is not exactly 1:2 but slightly larger, whereas it is often smaller than 1:2 for nonmusicians (Repp, London, & Keller, 2011, 2012. The reasons for these deviations from the exact simple (i.e., small-integer) ratio are not yet fully understood.…”
mentioning
confidence: 97%
“… 1 In a synchronization task, Repp et al (2011) observed non-integer ratios around 44% to be significantly distorted toward 33%, which may be a range effect, given repeated exposures and attempts to synchronize with patterns featuring subdivisions nearer to 33% in that experiment (see also Repp et al, 2012). In addition to the present study, others have observed ratios around 43% distorted toward 50% (e.g., Snyder et al, 2006).…”
mentioning
confidence: 91%
“…Phase space plots of durational structure in rhythmic patterns. One iteration (column i), and three iterations with random noise (similar overlaid polygons, column ii) and accelerando (similar smeared polygons, column iii) (Repp, London, & Keller, 2012). The number of edges in a polygon describes the number of IOIs in the temporal sub-pattern, in this case: two notes of alternating length (row A); repeating patterns of length three (B), four (C), and five (D) IOIs.…”
Section: Limitationsmentioning
confidence: 99%